FRI0573 Osteocytes are involved in the pathogenesis of osteoporosis in chronic cholestasis. effects of bilirubin and bile acids on osteocytic cell lines. (15th June 2017) - Ruiz-Gaspà, S; Parés, A; Combalia, A; Peris, P; Monegal, A; Guañabens, N
Abstract : Background: Mechanisms underlying osteoporosis in chronic cholestasis are complex and poorly understood. In this setting, osteoporosis mainly results from low bone formation, related to the effects of retained substances of cholestasis, such as bilirubin and bile acids. Thus, in "in vitro" studies, unconjugated bilirubin and serum from jaundiced patients decrease osteoblast viability, differentiation and mineralization. However, the influence of cholestasis on osteocytes, the most ubiquitous cells of the skeleton, is unknown. Objectives: The aim of this study was to analyze the direct effects of increased molecules of cholestasis, such as bilirubin (Bil) and lithocholic acid (LCA), and the potential protective effect of ursodeoxycholic acid (UDCA) on the osteocytes. Methods: MLO-Y4 and MLO-A5 osteocyte cell lines treated at different times and concentrations with Bil, LCA and UDCA were used to determine: 1) Viability: WST colorimetric method; 2) Differentiation: quantification of alkaline phosphatase (AP) activity; 3) Mineralization: Alizarin red staining quantification; and 4) Apoptosis: quantification of DNA fragmentation and caspase-3 activity. Results: LCA (100μM) and Bil (50μM) significantly decreased viability in MLO-Y4 from 72 hours (10%) and 48 hours (11%), respectively (p≤0.01), and Bil decreased viability (49%) in MLO-A5 from 96 hours (p<0.01). Bil decreased AP activity by 47% after 96 hours, under conditions of differentiation in MLO-Y4 (p≤0.01). There were no effects on AP activity in MLO-A5. After 14 days, Bil was associated with a significant mineralization decrease, as high as 87%, in MLO-A5 (p≤0.02). Moreover, Bil and LCA increased apoptosis in MLO-Y4, determined by DNA fragmentation (242% and 119%, respectively) and caspase-3 activity (190% and 251%, respectively) (p≤0.01) after 24 hours. In contrast, UDCA (100 μM) increased viability after 72 hours (11%) and decreased the deleterious effects of LCA or BiI (p≤0.02). UDCA increased AP activity in MLO-Y4 after 72 hours under growth conditions (p=0.018), and after 24 hours under differentiation conditions (p≤0.01). Conclusions: Bilirubin and lithocholic acid have damaging effects on osteocytic cells decreasing viability, differentiation and mineralization, and increasing apoptosis, effects that are neutralized by the UDCA. These results indicate that substances retained in cholestasis impair osteocytic functions, and therefore may be involved in the pathogenesis of osteoporosis in cholestatic diseases. Disclosure of Interest: None declared